PERSPEKTIF PERBUATAN MELAWAN HUKUM OLEH PEJABAT PUBLIK DALAM TINDAK PIDANA KORUPSI (Jurnal Konstituen, 2021)
The state of Indonesia is a state of law, this is written in Article 1 paragraph (3) of the Undang-Undang Dasar Negara 1945 Constitution. It means that the public, officials, military and non-military must obey and obey the law. The purpose of this study is to analyze the perspective of unlawful acts by public officials in corruption. The number of corruption cases in Indonesia throughout the year indicates that many sabats commit acts against the law. Against the law in the context of Law Undang-Undang Nomor 31 tahun 1999 as amended by Law Undang Nomor 20 tahun 2001 concerning the Eradication of Criminal Acts of Corruption, is classified as a criminal act or formal offense, in which the elements of the act must have been fulfilled, and not as material offense, which requires that the result of the act in the form of the resulting loss must have occurred. Talking about unlawful acts, corruption is included in the category of unlawful acts to enrich oneself, or other people or corporations and can harm state finances.Keywords: Unlawful Acts, Officials, Corruption Crimes